Juventudes e violência urbana: trajetórias de sujeitos em cumprimento de medida socioeducativa na cidade de Fortaleza - Pinheiro, Jéssica Pascoalino (2018)
The theme of urban violence has been increasingly invoked in different contexts, such as mass media, electoral campaigns, platforms of government, debates between jurists and public security experts and in the scope of studies of different academic areas, such as Psychology and Sociology. In this scenario, it is usual to emphasize topics that highlight infractions practiced by children and youth segments, while the violence of which these segments are victims is not addressed. In an attempt to counteract such silencings, this work has the general objective of: Analyzing relations between youths and urban violence produced in the narratives of young people in fulfillment of socio-educational measure of open-environment in the city of Fortaleza concerning their life trajectories. This objective presents itself as a possible way to analyze how urban violence intertwines with the lives of young perpetrators of infractions, both in terms of the violence they perpetrate and in terms of violations of rights that express the violence of the State and the society directed to these population segments. The specific objectives of this dissertation can be stated as follows: 1) Problematize how territorial conflicts and inscriptions in urban violence dynamics cross the juvenile experiences of subjects who are attributed the commission of an infraction; 2) Analyze discursive productions concerning the presence of institutional violence in the trajectories of subjects in compliance with socio-educational measures; 3) Think over contexts and experiences of compliance of socio-educational measures based on the juvenile trajectories investigated. This work carried out articulations with the studies of Foucault, Agamben, Deleuze, Guattari, Butler, Mbembe and authors of the Social Psychology field that follow similar paths, establishing the cartography as a research-intervention method. The research took place at the Urban Center of Culture, Art, Science and Sport (CUCA) located in Barra do Ceará/ Fortaleza. The participants of this study are youngsters from 15 to 17 years old in compliance of socio-educational measures of open-environment (CSP) inserted at the CUCA/ Barra do Ceará during the operation of this research, having participated in the discussion group held in 2017.1. In addition to the discussion group, it was decided to carry out the triangulation of methodological tools, to highlight: a) daily life conversations; b) narrative interview; c) a discussion group based on themes related to the human rights field chosen by the youngsters. Regarding the first specific objective, it is emphasized that in the War on Drugs the youth so-called "offender" incarnates the figure of the social enemy. A minorist logic is perpetuated by framing youth from the periphery as drug dealers and, therefore, as a matter of public safety, are seen as those who attack the well-being of "good citizens". The visibility of its existence is given by the prism of the infraction, of the violation of the rights of the other, visibility that places its juvenile trajectories as social counter-models (SALES, 2004). The drug trafficking is expressed as a mean of insertion of the young people living in periphery in the "world of work" through an informal and extremely precarious activity. Regarding the second specific objective, the figure of the "young person involved" is expressed as the public enemy, constituting itself as an identity for extermination in contexts of militarized public security policies, as Benicio and Barros (2017) points out. A permanent state of emergency is put in place which puts the rights of certain citizens under threat. The state of exception is now set as a contemporary government technique (AGAMBEN, 2004). The institutional violence in the daily life of black and peripheral youths, such as police violence and the perpetuation of racism is presented by Barros et al. (2018) as an expression of a necropolitics, political technology of production and management of death of unwanted lives, permeated by processes of racialization and production of "enemies" to be annihilated, in favor of social security. Finally, regarding the third specific objective, it is noted that the continuous disinvestment of the socio-educational potential of the open-environment measures perpetuates a punitive logic for the so-called "juvenile offenders". It can be seen that the greater deliberation of measures of deprivation of liberty for juvenile offenders indicates a process of devaluation (and, if not, boycotting) of the potential responsible of the open-environment measures, which makes it possible to redefine juvenile trajectories marked by violence, disinvestment and abandonment. What, then, means the socio-education? Which is the meaning that young people attribute to youth accountability?